The Influence of Price, Service Quality and Product Quality on Customer Satisfaction at Elflorist Boyolali - Vicky Surya Sajarwo; Triyanto, Triyanto (Cita konsultindo, 2025)
This study examines the influence of price, service quality, and product quality on customer satisfaction at Elflorist Boyolali. Using a quantitative approach, the study involved 40 customers selected through convenience sampling techniques. Data were obtained from questionnaires and analyzed by multiple regression method. The results of the analysis show that price significantly and positively affects customer satisfaction, the quality of the service significantly and positively affects customer satisfaction, and the quality of the product significantly and positively affects customer satisfaction. Partially, each variable has a significant contribution to improving customer satisfaction, while simultaneously, all three also have a significant effect. These findings confirm that these factors are the main determinants in building customer satisfaction at Elflorist Boyolali.